$S_n = 2S_{n-1} + S_{n-2}$
Characterstic polynomial for this recurrence is $x^2 = 2x + 1$
$x^2 - 2x - 1 = 0 \color{maroon}{\Rightarrow x_1 = (1+\sqrt{2}), x_2 = (1-\sqrt{2})}$
The solution to the recurrence relation is of the form : $S_n = C_1\times x_1^n + C_2\times x_2^n$
Putting $S(0) = 0$, $\color{blue}{C_1 + C_2 = 0}$
Putting $S(1) = 1$, $\color{blue}{C_1\times (1+\sqrt{2}) + C_2\times (1-\sqrt{2}) = 1}$
Solving these two, we get $C_1 = \frac{1}{2\sqrt{2}}$ and $C_2 = -\frac{1}{2\sqrt{2}}$
$\large S_n = \frac{1}{2\sqrt{2}} \bigg((1+\sqrt{2})^n - (1-\sqrt{2})^n\bigg)$
$\color{navy}{S_0 = 0, S_1 = 1, S_2 = 2, S_3 = 5, S_4 = 12, S_5 = 29, S_6 = 70}$
Clearly $S_3$ and $S_6$ are not a multiple of $3$
Hence (C) is correct answer.